International Assessment and Framework for Gender Equality - Asawasakulkrai, Angkana (NIDA Development Journal, 2023)
This study investigates the gender-related issues that impede women and girls’ abilities to survive and thrive. These issues – poverty, education, employment, violence, stereotypes, and political participation – prevent women and girls from becoming a healthy and productive member of society. Despite the world’s progress in all avenues, not all women and girls enjoy basic human rights and opportunities that are afforded to men and boys. In this capacity, there have been a number of international assessments, frameworks, indicators, and indices invented for the assessment of gender equality. These methods share the same purposes of assessing the status of gender equality, predicting the trajectories of future gender equality, and hopefully serving as a foundation for policy formulation to create a more inclusive society. This study therefore examines the methods and approaches used from past to present to assess the global landscape of gender equality. The examination and analysis find that while the frameworks and indices may serve as a useful lens reflecting to a certain extent the gender equality status in different countries, often times they fail to grasp contextual differences and the complexity and variability of the real gender-related issues among regions and countries. Therefore, while these assessments are well-intended, the efforts should continue to be the improvement, refinement, and expansion of areas to be included and measured. In addition, a qualitative investigation should always be considered since gender issues are rigorously context-specific and not always quantifiable.